2021
DOI: 10.3390/cancers13112544
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared Fluorescence Imaging of Intraperitoneal Ovarian Tumors in Mice Using Erythrocyte-Derived Optical Nanoparticles and Spatially-Modulated Illumination

Abstract: Ovarian cancer is the deadliest gynecological cancer. Cytoreductive surgery to remove primary and intraperitoneal tumor deposits remains as the standard therapeutic approach. However, lack of an intraoperative image-guided approach to enable the visualization of all tumors can result in incomplete cytoreduction and recurrence. We engineered nano-sized particles derived from erythrocytes that encapsulate the near infrared (NIR) fluorochrome, indocyanine green, as potential imaging probes for tumor visualization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…RBCs are disciform with a hollow center, allowing resistance to osmotic pressure or external shock and flexibility to pass through the capillary. RBC membranes were extensively used for modifying nanoparticles due to their ability to avoid the immune system and achieve long-term circulation [2,25,[27][28][29][30][31]. For example, Hu et al [32] reported that RBC membrane-coated nanoparticles had significantly longer circulation time as compared to that of bare nanoparticles or RBC membrane vesicles.…”
Section: Natural Cell Membranes and Their Unique Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…RBCs are disciform with a hollow center, allowing resistance to osmotic pressure or external shock and flexibility to pass through the capillary. RBC membranes were extensively used for modifying nanoparticles due to their ability to avoid the immune system and achieve long-term circulation [2,25,[27][28][29][30][31]. For example, Hu et al [32] reported that RBC membrane-coated nanoparticles had significantly longer circulation time as compared to that of bare nanoparticles or RBC membrane vesicles.…”
Section: Natural Cell Membranes and Their Unique Featuresmentioning
confidence: 99%
“…The advent of cell membrane cloaking technique in cancer nanotechnology bestows nanoparticles with extended blood circulation period, enhanced immune evasion, localized drug delivery, improved tumor penetration, and accumulation [43,106]. Nanoparticles with a high capacity of anti-cancer drug loading and photodynamic properties were decorated with cell membranes isolated from various cell types, including cancer cells, fibroblasts, platelets, macrophages, RBCs, white blood cells, dendritic cells, and natural killer (NK) cells [7,23,24,27,29,31,107,108]. Cell membranes obtained from cancer cells and immune cells were extensively used especially for cancer immunotherapy due to their inherent immune evasion and homologous tumor-targeting ability [49,109].…”
Section: Cancermentioning
confidence: 99%
“…We refer to these particles as microsized NIR erythrocyte-derived transducers (μNETs) as they can transduce NIR light to emit fluorescence, generate heat, or produce reactive oxygen species. , We have previously investigated the use of μNETs for real-time intravascular fluorescence imaging and photothermal destruction of the microvasculature, similar to vascular malformations found in port wine stain lesions . ICG-doped RBCs have been used to characterize microvascular vasomotion in humans. , We have used nanosized RBC-derived particles containing ICG for NIR fluorescence imaging and photodestruction of tumors in animal models. , The present study is an important step towards the engineering of RBC-derived particles with appropriate biochemical characteristics, based on cholesterol incorporation, to enhance the bioavailability of the particles resulting from reduced clearance by the immune cells. Membrane cholesterol enrichment is also relevant to the fabrication of RBC-based particles containing not only optical materials but also other types of biomedical cargos. , …”
Section: Introductionmentioning
confidence: 99%
“…15,16 We have used nanosized RBC-derived particles containing ICG for NIR fluorescence imaging and photodestruction of tumors in animal models. 5,40 The present study is an important step towards the engineering of RBC-derived particles with appropriate biochemical characteristics, based on cholesterol incorporation, to enhance the bioavailability of the particles resulting from reduced clearance by the immune cells. Membrane cholesterol enrichment is also relevant to the fabrication of RBC-based particles containing not only optical materials but also other types of biomedical cargos.…”
Section: ■ Introductionmentioning
confidence: 99%
“…9 In order to show ovarian tumours clearly by NIR fluorescence imaging during operation, some nanoparticle probes have been designed and achieved excellent results in basic experimental stage. [10][11][12][13] A Phase II clinical trial indicated that OTL38, which consists of folate conjugated to an indocyanine green-like (excitation at 776 nm, emission at 796 nm) near-infrared fluorescent dye termed S0456, was more effective in detecting tumours when using NIR fluorescent imaging during surgery. At least one additional lesion was detected in 48.3% of patients (14/29) by using OTL38-mediated near-infrared fluorescence imaging, but the tumour-to-background fluorescence signal ratio (TBR) of OTL38 was 4.4±1.4.…”
Section: Introductionmentioning
confidence: 99%